Productive, morfhogenic and structural characteristics of Brachiaria brizantha cultivars grown in two types of soil (Research, Society and Development, 2020)
The objective of this study was to evaluate the effect of two distinct soils on the productive, morphogenic and structural characteristics of two cultivars of Brachiaria brizantha. The experiment was conducted in a completely randomized design with three replications. The treatments consisted of two cultivars (Piatã and Marandu) and two soils (Cambissolo and Argisolo), in a 2 x 2 factorial arrangement. There was no interaction (P>0.05) between the factors. Soil type and cultivar did not affect (P>0.05) the morphogenic and structural characteristics of the grasses. There was an effect (P0.05) by soil type. Grasses had higher growth and were more productive when grown in Cambisol. The cv. Marandu presented higher tillering in detriment of the smaller growth in height in relation to the cv. Piatã.